Twice as Nice: The Duff Formylation of Umbelliferone Revised - Vladislav V. Skarga; Vadim V. Negrebetsky; Yuri I. Baukov; Mikhail V. Malakhov (Molecules, 2021)
More efficient and preferably more convenient and greener synthetic solutions in coumarin scaffold functionalization are in steady demand. The Duff ortho-formylation of unsubstituted umbelliferone was revised in this study. The reaction conditions were optimized based upon data from the literature analysis and resulted in unexpectedly rapid ortho-formylation of umbelliferone, yielding a mixture of ortho-formyl position isomers. Thorough studies on the separation of ortho-formylated umbelliferones using chromatographic and recrystallization methods as well as the evaluation of their solubility in common organic solvents led to complete resolution of 8-formyl- and 6-formylumbelliferones. The precise protocol for simultaneous preparation, extraction, and purification of 8-formyl- and 6-formylumbelliferones is provided, and the prospective studies of biological and pharmacological activities of these compounds are synopsized.